BIG FIVE PERSONALITY TERHADAP KOMITMEN ORGANISASI DOSEN UNIVERSITAS NEGERI JAKARTA - MAUNA MAUNA; MUHAMMAD ISHAK SHABUR (Journal of Research and Measurement in Psychology, 2017)
This study aims to determine the effect of big five personality on organizational commitment toward the lecturers State University Of Jakarta. Personality trait is composed of five major trait that Opennes to Experience, Conscientiousness, Extraversion, Agreeableness and Neuroticism (OCEAN). The fifth trait of the personality trait will be seen any where that has an influence on the organizational commitment of the lecturers in Universitas Negeri Jakarta. This research method using quantitative methods. The sampling technique used is insidental sampling. In the process of the data used comes from the true score of Rasch modeling. The measuring tool used for organizational commitment is the Organizational Commitment Questionnaire whichis constructed by Meyer and Allen with reliability value of items of 0.97 based on Rasch Modeling. For measuring personality trait is used The Big Five Inventory who constructed by John et al. With the reliability value items amounted to 0.99 based on Rasch modeling. In the data processing used multiple regression model. Based on the result, obtained the value of p = 0,000 < 0.05 (significant), meaning that thefive personality trait had an influence (13,1%) on organizational commitment, only trait Extraversions and Conscientiousness, while trait opennes to Experience, Agreeableness and Neuroticism did not have effect.